2012 IEEE Sensors 2012
DOI: 10.1109/icsens.2012.6411311
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogen detection of Pd/AlGaN/GaN HEMT-type sensors by temperature sweep operation

Abstract: We have demonstrated the selective hydrogen gas detection of Pd/AlGaN/GaN high electron mobility transistors-based hydrogen sensors by the temperature sweep operation. The sensitivity-temperature spectra of the Pd/AlGaN/GaN HEMT hydrogen sensors in the range of 30°C to 350°C were measured in hydrogen, methane and propane with various concentrations of diluted with nitrogen. It is found that the different gases have the characteristic sensitivitytemperature spectra with the different peak positions, which is du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…2(d)). 85 They found that each gas had a characteristic spectrum of sensitivity to temperature at different peak positions owing to their different decomposition temperatures. When the gas concentration was 1000 ppm, the highest response sensitivities of H 2 , CH 4 , and C 3 H 8 were all around 0.78, but the optimized temperatures at their maximum sensitivity were 230 °C, 350 °C, and 310 °C, respectively.…”
Section: Types Of Gan-based Gas Sensorsmentioning
confidence: 99%
“…2(d)). 85 They found that each gas had a characteristic spectrum of sensitivity to temperature at different peak positions owing to their different decomposition temperatures. When the gas concentration was 1000 ppm, the highest response sensitivities of H 2 , CH 4 , and C 3 H 8 were all around 0.78, but the optimized temperatures at their maximum sensitivity were 230 °C, 350 °C, and 310 °C, respectively.…”
Section: Types Of Gan-based Gas Sensorsmentioning
confidence: 99%